Morphological and molecular characterization of the rice root-knot nematode, Meloidogyne graminicola, Golden and Birchfeild, 1965 occurring in Zhejiang, China - Zhong-ling TIAN; Munawar Maria; Eda Marie Barsalote; Pablo Castillo; Jing-wu ZHENG (Journal of Integrative Agriculture)
The rice root-knot nematode Meloidogyne graminicola is a severe pest of rice. In China, it was first reported from Hainan Province, and later from several other provinces. In the present study, a rice root-knot nematode population found from the rice cultivation areas of Zhejiang Province, China is characterized via molecular analysis using internal transcribed spacer (ITS) and cytochrome c oxidase subunit II (coxII)-16S rRNA genes and scanning electron microscopy (SEM) observations of males and the second-stage juveniles. Morphometric data and molecular sequence comparisons for all M. graminicola populations occurring in China are also provided. The overall morphology of M. graminicola found in Zhejiang match well with the original description, though males have a slightly longer body and stylet, and a shorter tail, while the second-stage juvenile is also slightly longer than in the original description. This is the first report of M. graminicola from Zhejiang. Phylogenetic studies based on coxII suggest that all the Chinese populations belong to Type B. This study expands knowledge of the increasing distribution and phylogenetic relationships of M. graminicola that occur in China.